How endocrine disruptors affect fish reproduction on multiple levels: A review - Socha Magdalena; Chyb Jarosław; Suder Aleksandra; Bojarski Bartosz (Fisheries & Aquatic Life)
This review paper presents fish reproductive toxicology studies with a specific focus on endocrine-disrupting chemicals (EDCs) present in the aquatic environment. These substances, including bisphenols, heavy metals, pesticides, phthalates, and polychlorinated biphenyls (PCBs), act as hormone mimics, receptor blockers, or enzyme inhibitors that affect hormonal regulation in the hypothalamic-pituitary-gonadal (HPG) axis. In this review, we provide an overview of the adverse effects of these pollutants on both female and male fish reproduction (i.e., hormonal disruption in the HPG axis, gametogenesis disorders, disturbed embryogenesis, etc.). Even at low concentrations, EDCs can exhibit reproductive toxicity in fishes. They can affect the functioning of certain systems within the hypothalamus (Kiss/GPR54, GnRH) and can also impact luteinizing hormone (LH) secretion in the pituitary. These compounds have negative impacts on gonads, oocyte maturation, steroidogenesis, and gametes. Early-life exposure to these substances not only affects embryonic development, resulting in increased mortality and body malformations, but this also induces genetic changes in newly hatched larvae. All these observations underscore the need for monitoring the aquatic environment for EDCs and implementing protective measures to preserve the health and welfare of fishes and safeguard water ecosystems.